The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1523/jneurosci.3154-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Single Seizure Episode Leads to Rapid Functional Activation of KCC2 in the Neonatal Rat Hippocampus

Abstract: Functional expression of the K-Cl cotransporter KCC2 in developing central neurons is crucial for the maturation of Cl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 43 publications
4
97
0
Order By: Relevance
“…transporter proteins, including NKCC1 and KCC2 (Rivera et al, 2004;Jin et al, 2005;Dzhala et al, 2010;Khirug et al, 2010). However, we found that adenosine had no direct effect on steadystate E GABAA or the recovery of depolarizing GABA A R responses back to hyperpolarizing.…”
Section: Discussionmentioning
confidence: 61%
“…transporter proteins, including NKCC1 and KCC2 (Rivera et al, 2004;Jin et al, 2005;Dzhala et al, 2010;Khirug et al, 2010). However, we found that adenosine had no direct effect on steadystate E GABAA or the recovery of depolarizing GABA A R responses back to hyperpolarizing.…”
Section: Discussionmentioning
confidence: 61%
“…Imposing a defined somatic Cl Ϫ load via the patch pipette enables assessment of the efficacy of Cl Ϫ extrusion. As shown previously (Khirug et al, 2005(Khirug et al, , 2008(Khirug et al, , 2010Blaesse et al, 2006;Li et al, 2007;Gauvain et al, 2011), functional expression of KCC2 results in a somatodendritic gradient of [Cl Ϫ ] i , which can be measured as a gradient in E GABA between the somatic and dendritic compartments (⌬E GABA ). Notably, control levels of ⌬E GABA remained unchanged for the experimental duration of 0 -4 h (0 -2 h: Ϫ6.05 Ϯ 0.31 mV/50 m; n ϭ 12 cells; 3-4 h: Ϫ6.28 Ϯ 0.28 mV/50 m; n ϭ 14 cells).…”
Section: Total Block Of Protein Synthesis Does Not Affect Kcc2 Proteimentioning
confidence: 63%
“…In some experiments, calpain-2 was preincubated with 100 M MDL-28170 for 5 min. (Khirug et al, 2010;Ahmad et al, 2011) was used to analyze the surface expression of KCC2. Briefly, transverse hippocampal slices were treated with cod trypsin (Zymetech), a protease that retains its activity at low temperatures while trafficking of membrane proteins is blocked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that nerve injury reduces KCC2 protein levels and synaptic inhibition in the spinal cord through activation of NMDARs and subsequent Ca 2ϩ influx. Nerve Injury Induces Proteolysis of KCC2 at the C Terminus through NMDAR Activation-The KCC2 protein is present in both the plasma membrane and cytoplasmic fractions (12,34). To determine whether nerve injury alters the subcellular distribution of KCC2 in the spinal cord, we analyzed the protein level of KCC2 in the plasma membrane and cytosolic fractions in the dorsal spinal cords of SNL rats.…”
Section: Nerve Injury Switches Glycine-mediated Synaptic Inhibition Tmentioning
confidence: 99%